Microgomphus alani (Odonata, Gomphidae) sp. nov. from Cambodia - Kosterin, Oleg E. (Zootaxa, 2016)
Microgomphus alani sp. nov. is described from two males from the coastal southwestern foothills of the Cardamom Mts. in southwestern Cambodia (type locality: Cambodia, Koh Kong Province, 17 km ENE of Koh Kong, ‘Macromia Rivulet’, 11°40'17'' N, 103°07'28'' E, 296 m a.s.l., 3 vi 2014, RMNH). The species is characterised by its small size (hindwing 21–23 mm), cerci with outer angulations, truncated apices and crescent-shaped inner arms sprouting from their middle and not reaching their apices, synthorax with two parallel black lateral stripes and dorsal and collar yellow stripes fused in 7-like manner. Probably females of the same species were earlier reported from Phrae Province in northern Thailand.